A death in the family: Citizens' experiences of changing healthcare commissioning practices in South East England. (19th May 2020) - Graber, Rebecca; Zoli, Anna; Walker, Carl; Artaraz, Kepa
Abstract: The Brighton Citizens Health Services Survey was an academic activism project to identify and understand citizens' perceptions of and responses to healthcare commissioning practices. Significant legislated changes to the National Health System (NHS) across England have increased marketisation in healthcare provision, yet little research has explored the psychological dimensions of this shifting context and its community impact. Taking a community psychological perspective to social policy, we aimed to understand lay citizens' lived experience of changes in healthcare commissioning and provision. Thematic analysis of 379 free‐text responses yielded two thematic clusters. Cluster 1 describes the lived experience of citizens considering reforms to the NHS, depicting grief, mortality and fear in uncertainty. Cluster 2 explores where these affective responses may derive from by detailing conceptualisations of the NHS in the lived experience, describing how the NHS was experienced as a complex and embodied phenomenological object. Findings suggest people relate affectively to local commissioning practices, feeling a sense of loss when facing the degradation of 'their' NHS. We argue that an affective relational perspective centres important questions of silencing, voice‐giving, meaningful engagement and ways of knowing that in turn impact the landscape of community health.